Postoperative chylous ascites after total gastrectomy successfully treated using peritoneovenous (Denver) shunt: a case report - Shinya Sakamoto; Nobuo Takata; Yoshihiro Noda; Kazuhide Ozaki; Takehiro Okabayashi (Surgical Case Reports, 2022)
Abstract Background Chylous ascites (CA) is a rare complication of gastrectomy for gastric cancer. While most cases of postoperative CA improve with medication or nutritional support, some are refractory to conservative treatment. A peritoneovenous shunt (PVS) may help patients who are poor candidates for surgery. However, PVS placement for postoperative CA after gastroenterological surgery has been rarely reported. Herein, we present a case of postoperative CA following total gastrectomy with para-aortic lymphadenectomy, treated successfully by PVS placement. Case presentation A 74-year-old man who underwent total gastrectomy with para-aortic lymph node dissection was hospitalised because of insufficient oral intake and dehydration. His abdomen was markedly distended with severe bilateral lower extremity oedema. On admission, abdominal computed tomography (CT) showed a high volume of ascites and no signs of cancer recurrence. Accordingly, postoperative CA resulting from drainage of fluid on paracentesis was diagnosed. Despite nutritional support, diuretics, and octreotide administration, his abdominal distension and nutritional status did not improve. We could not identify the sites of lymphatic leakage in the three intranodal lymphangiographies followed by CT. Although we considered a surgical treatment in our patient, we decided against it. Because we could not identify lymphatic leakage site during lymphangiography, surgical treatment might have a potential failure of detection and closure of leakage site. Furthermore, the patient’s general condition was poor because of malnutrition resulting from the loss of lymphatic fluid. Consequently, we decided to place PVS. After PVS placement, his abdominal distension improved rapidly, and he was discharged without serious complications. Thirteen months after PVS, patient has no relapse of abdominal distention and nutrition status has improved. Conclusion PVS might be a good option to manage refractory postoperative CA, as the leakage point cannot be detected on lymphangiography.